Process for construction of rating scales according to the Likert technique - Hernandez Valz, Héctor (2000)
In this article it is presented the technique succinctly to elaborate scales of valuation in those that values are measured referred to specific behaviours, The starting point is the comparison among three definitions lo illustrate the character of feeling of the values to opt at the end for the definition of Rokeach, according to which uses the technique of Likert and each article contains the comparison between the selected value and a value competitor, assisting lo the definition of Rokeach according to which a value is a relatively permanent belief That a way of particular behaviour or that an existence state is personal and socially preferable to alternating ways of behaviour and existence states». Of definition is he/she has taken as approach for the construction from the items to the preference notion. Next the steps are presented to give from the moment in That the values are chosen that you/they will measure.